Vpliv ravni in obsega okvare hrbtenjače na funkcijski izid rehabilitacije in trajanje hospitalizacije pri bolnikih z okvaro hrbtenjače - Rode, Neža (Rehabilitacija (Ljubljana), 2014)
Background: The aim of the study was to investigate the effect of level and extent of spinal cord injury on the functional outcome of spinal cord injured patients in different time periods of in-patient rehabilitation, and on the length of stay at the Department for Rehabilitation of Patients with Spinal Cord Injury of the University Rehabilitation Institute in Ljubljana, Slovenia. We were also interested in the proportion of functional outcome at discharge that patients achieved after six weeks of in-patient rehabilitation. Methods: The study included all the patients who were admitted to our department for the first time in the period from 1 June 2010 to 31 December 2013. Additional inclusion criteria were at least six weeks of hospitalization and a completed rehabilitation program at discharge. The patients were required to have a complete SCIM (Spinal Cord Independence Measure) assessment upon admission, after six weeks and at discharge. Patients were divided into four groups according to the level and extent of spinal cord injury. Results: The inclusion criteria were met by 109 patients. The average SCIM score at the end of treatment was statistically significantly (p0.05) in all groups of patients over all three periods of assessment. After six weeks, all patients achieved more than 70 % of the SCIM score at discharge. Patients with complete cervical spinal cord injury had longer length of stay than those with incomplete injury. Conclusions: The level and extent of spinal cord injury affect the functional status of patients throughout their hospitalisation. During inpatient rehabilitation, all the four patient groups achieved similar functional improvement despite the different functional status at the beginning of rehabilitation and different length of stay.
Keywords: ASIA; functional outcome; functional progress; funkcijsko izboljšanje; funkcijsko stanje; okvare hrbtenjače; rehabilitacija; Spinal Cord Independence Measure; Spinal Cord Injuries; vocational rehabilitation